Efficient Technique for Providing Authentication of Short Encrypted Messages (International Journal of Engineering and Computer Science, 2015)
with the advancement in the technology, many of the applications depend on the existence of the small devices to communicate by exchanging messages. In such applications, the messages exchanged are short. The confidentiality and integrity of communicated short messages is of at most important in such applications. Here in this paper, we propose two new techniques for authenticating short encrypted messages that meets the requirement of such applications. The basic notion behind the proposed techniques is exploiting the security that the encryption algorithm provides to design an authentication mechanism that is more efficient than the existing authentication technique in the literature of cryptography.